MicroRNA-122 protects against interferon-α-induced hepatic inflammatory response via the Janus kinase–signal transducer and activator of transcription pathway - Fanwei Liu; Bowen Liu; Shanshan Xu; Yinhua Ni; Xiaoli Liu (Endocrine Journal)
Significant overlap in the epidemiology and coinfection of chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) has been identified, which accelerates the development of severe liver cirrhosis and hepatocellular carcinoma worldwide. Interferon-α (IFN-α), a cytokine with antiviral properties, exerts profound physiological effects on innate immunity by regulating interferon-stimulated genes (ISGs) within cells. However, the underlying mechanism of IFN-α in hepatic inflammation remains to be fully elucidated. Here, we utilized LO2 cells treated with the recombinant IFN-α protein and conducted microRNA (miR) sequencing. MiR-122-3p and miR-122-5p_R+1 were the most enriched miRNAs involved in the pathogenesis of IFN-α-induced inflammatory responses and were significantly downregulated by IFN-α treatment. Furthermore, we identified interferon induced protein with tetratricopeptide repeats 1 (IFIT1) as a potential target gene of miR-122. IFN-α markedly increased the expression of proinflammatory cytokines and fibrogenic genes but decreased the mRNA expression of ISGs. Additionally, IFN-α significantly activated the NF-κB p-p65, MAPK p-p38, and Jak/STAT pathways to trigger inflammation. Importantly, supplementation with a miR-122 mimic significantly alleviated IFN-α-induced inflammation and induced IFIT1 expression in LO2 cells. Conversely, the suppression of miR-122 markedly exacerbated the inflammatory response triggered by IFN-α. Furthermore, silencing IFIT1 via an siRNA elicited an inflammatory response, whereas IFIT1 overexpression ameliorated hepatic inflammation and fibrosis in a manner comparable to that induced by IFN-α treatment. Taken together, our findings suggest that miR-122 and its target, IFIT1, reciprocally regulate the inflammatory response associated with IFN through the Jak/STAT pathway.